Improving the Ability of Teachers to Teach Social Studies Subjects Through the Application of the Teams Game Tournament (TGT) Cooperative Learning Model for Fourth Grade Students of SD Negeri 13 Kabawo - Nurni (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
This study aimed to increase teachers' ability to teach social science subjects through a team game tournament (TGT) cooperative learning model for fourth-grade students of SD Negeri 13 Kabawo. This type of research is school action research (PTS). The implementation procedure consists of four stages: planning, implementing actions, observing and evaluating, and reflecting. The results showed that student learning outcomes in the first cycle of students who obtained a score of 70 or completed as many as 11 people (61.11%) and those who had not completed as many as seven people (38.89%) in the second cycle who completed as many as 16 people (88, 89%) and two people (11.11%). The number and percentage of students who finished studying social studies subjects increased in cycle II, and the learning process for grade IV students at SD Negeri 13 Kabawo had been completed. The implementation of the learning scenario carried out by the teacher when teaching in the first cycle was 65.9%, and in the second cycle, it was 86.35% and has reached the implementation standard that has been set, which is 80%. Student learning activities also experienced similar results; student activity in the first cycle was 53.6% and increased in the second cycle to 85.7% and was said to be completely based on the KKM. Applying the cooperative learning model of the Teams Game Tournament (TGT) type in social studies subjects can improve the teaching abilities of fourth-grade teachers at SD Negeri 13 Kabawo.